The Accuracy of an Intraoperative Frozen Section for PremalignantEndometrial Pathology - (:unkn) unknown (My University, 2020)
OBJECTIVE: Abnormal uterine bleeding which is the most frequent complaint among pre- and post-menopausal women should be investigated to rule out endometrial cancer. An intra-operative frozen section can be taken to examine the suspicious of the malignancy. The study aims to investigate the ac-curacy of frozen section in suspicious of endometrial malignancy. STUDY DESIGN: Fifty patients with pre-malign endometrial pathology and malignant ultrasound char-acteristics were included in this study and their preoperative biopsy, frozen and postoperative patholog-ical results were examined. RESULTS: The kappa coefficient between postoperative pathology and frozen section was 0.88 (p<0.05) and 95% confidence interval was (0.63-1.12). This indicates that the amount of agreement be-tween the two tests was strong, thus the frozen section would be considered as a valid indicator of post-operative pathology results. CONCLUSIONS: Frozen section is a valuable method to investigate the suspicious of malignancy in en-dometrial pre-malign lesions.